Adrenal incidentalomas, cortisol secretion and cancer: is there a real crosstalk? - Herrera-Martínez, Aura D.; Román, Ángel Rebollo; Corrales, Eider Pascual; Idrobo, Cindy; Ramírez, Paola Parra; Rojas, Patricia Martín; Lázaro, Cristina Robles; Araujo-Castro, Marta (Frontiers in Endocrinology, 2024)
Background: Cortisol has immunomodulatory effects that increase the risk and evolution of several diseases. Cancer is characterized by a proinflammatory state in which cells exert impaired function and proliferation. The relation between cortisol secretion and increased risk of malignant neoplasm, or their behavior, has not been fully elucidated.Aim: To determine the relation between cortisol secretion and the prevalence and clinical outcome of malignant neoplasms in patients with adrenal incidentalomas (AIs).Methods: Multicenter retrospective study that included 935 patients with AIs. Cortisol secretion was defined by a cortisol post-dexamethasone suppression test > 1.8 µg/dL, and nonfunctioning AIs (NFAIs) as a value ≤ 1.8 µg/dL.Cortisol secretion was evident in 30.8% of the patients and cancer in 23.6% (especially breast, colorectal, prostate and thyroid cancer). No differences in the cancer prevalence were found between patients with cortisol secretion and NFAIs (63.6% vs. 63.4%, p=0.10). After adjusting by age, cortisol secretion was not associated with the presence of cancer (OR 1.29, CI 0.93-1.78). However, cortisol secretion was significantly associated with stage IV of cancer at diagnosis (OR 2.68, CI 1.19-6.00) and mortality (OR 3.2,. Patients with NFAI and breast cancer required treatment with chemo-and radio-therapy more frequently that patients with cortisol secreting AI (90% vs 10% and 92.9% vs 7.1% respectively, p<0.05), similarly patients with prostate cancer required radiotherapy more frequently (90.9% vs 9.1%, p=0.05); also, patients with colorectal cancer and NFAI, tended to require chemotherapy more frequently(76.5% vs 23.5%, p=0.06).Cortisol secretion does not increase the risk of malignant neoplasm, but it affects its clinical course, treatment requirements and mortality, leading to a worst prognosis and higher mortality when compared with patients with NFAIs.